2012
DOI: 10.2903/j.efsa.2012.3017
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion updating the risk assessment conclusions and risk management recommendations on the genetically modified insect resistant maize MON 810

Abstract: Following a request from the European Commission, the Panel on Genetically Modified Organisms of the European Food Safety Authority (EFSA GMO Panel) compiled its previous risk assessment conclusions and risk management recommendations on the genetically modified insect resistant maize MON 810, and considered their validity in the light of new relevant scientific publications published from 2009 onwards. Following a search of the scientific literature published between 2009 and October 2012, the EFSA GMO Panel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 169 publications
0
3
0
Order By: Relevance
“…The immunogenic capacity of the Cry1Ab protein per se is wellknown and it has been described in previous studies (Adel-Patient et al, 2011). This has been previously assessed by the GMO Panel (EFSA GMO Panel, 2012b). Specific IgE antibodies against the purified Cry1Ab protein were observed by Andreassen et al (2015).…”
Section: 5mentioning
confidence: 99%
“…The immunogenic capacity of the Cry1Ab protein per se is wellknown and it has been described in previous studies (Adel-Patient et al, 2011). This has been previously assessed by the GMO Panel (EFSA GMO Panel, 2012b). Specific IgE antibodies against the purified Cry1Ab protein were observed by Andreassen et al (2015).…”
Section: 5mentioning
confidence: 99%
“…Guerrero et al, 2004;Adel-Patient et al, 2011) and the GMO Panel identified no indications of safety concern in the context of the applications assessed (EFSA GMO Panel, 2012, 2016a. 28 Sprayed once with glufosinate-ammonium-based herbicides and twice with glyphosate.…”
Section: Assessment Of Allergenicity Of the Newly Expressed Proteins 30mentioning
confidence: 99%
“…From a broader perspective, the effects on the immune system of Cry proteins, in particular Cry1Ac and Cry1Ab, have been investigated (e.g. Guerrero et al, 2004;Adel-Patient et al, 2011) and the GMO Panel identified no indications of safety concern in the context of the applications assessed (EFSA GMO Panel, 2012, 2016a. A recent study by Torres-Mart ınez et al (2016) involving the Cry1Ac protein was assessed by the GMO Panel.…”
Section: Assessment Of Allergenicity Of the Newly Expressed Proteins 30mentioning
confidence: 99%